Continuous bioethanol fermentation from wheat straw hydrolysate with high suspended solid content using an immersed flat sheet membrane bioreactor. (October 2017) - Mahboubi, Amir; Ylitervo, Päivi; Doyen, Wim; De Wever, Heleen; Molenberghs, Bart; Taherzadeh, Mohammad J.
Highlights: Immersed membrane bioreactor was used for continuous lignocellulosic bioethanol fermentation. The iMBR was optimized to work flawlessly at high suspended solid content (20%). Enhanced co-consumption of total glucose and up 83% xylose content was achieved. A bioethanol content of up to 83% of the theoretical yield was obtained. Abstract: Finding a technological approach that eases the production of lignocellulosic bioethanol has long been considered as a great industrial challenge. In the current study a membrane bioreactor (MBR) set-up using integrated permeate channel (IPC) membrane panels was used to simultaneously ferment pentose and hexose sugars to ethanol in continuous fermentation of high suspended solid wheat straw hydrolysate. The MBR was optimized to flawlessly operated at high SS concentrations of up to 20% without any significant changes in the permeate flux and transmembrane pressure. By the help of the retained high cell concentration, the yeast cells were capable of tolerating and detoxifying the inhibitory medium and succeeded to co-consume all glucose and up to 83% of xylose in a continuous fermentation mode leading to up to 83% of the theoretical ethanol yield.